Awareness and Knowledge of Glaucoma and it's Risk Factors among Visitors of Main Hospitals in Sanaa City, Yemen, 2025-2026 - Abdullah, Alaa Abdulkader Ahmed; Saad, Alaa Khalid Ali; Alzomoer, Afnan Ali Mohammed; Qaid, Bushra Abdulkareem; Alazzani, Eradah Hamod Abdo; Rageh, Somaia Abdu Alnaser Ahmed (My University, 2026)
Background: Glaucoma is a chronic progressive optic neuropathy and a leading cause of irreversible blindness worldwide. Despite the availability of effective management strategies, delayed diagnosis remains common due to inadequate public awareness and misconceptions about the disease. Objective: To evaluate the level of awareness and knowledge regarding glaucoma and to determine the association between knowledge level and sociodemographic characteristics among hospital attendees.